Impact of plyometric training and weight training on vertical jumping ability - Jaswant Thakur; Mukesh Mıshra; Vishan Rathore (Türk Spor ve Egzersiz Dergisi)
The Purpose of the study was to find out the comparative effect of Plyometric and weight training on vertical jumping ability. For the present study 24 male students from Department of Physical Education, BHU Varanasi were selected randomly as the subjects for the study. The age of the subjects ranged between 18 - 21 years. The variables selected for the present study were Plyometric and weight training (independent variable), vertical jumping ability (dependent variable). For the study pre test – post test randomized group design, which consists of control group (08 students) and two experimental groups (16 students) were used. The data were collected through the pre test, before training and post test, after six weeks of Plyometric and weight training. To find out the comparative effect of Plyometric and Weight Training on vertical jumping ability of the subjects the pre test and post test scores were analyzed by using Descriptive analysis, Analysis of Co-Variance (ANCOVA) and LSD test were used, the data analyzed with the help of SPSS (16.0 version) software and the level of significance was set at 0.05 level of confidence. The result of the study showed that there was significant difference between pre and post test (experimental group) of Jump amp; Reach and Approach Jump amp; Reach. Significant difference was found between adjusted means of Plyometric training and control group, weight training and control group in relation to jump and reach performance (p lt; 0.05). In relation to approach jump and reach performance significant difference was found between adjusted means of Plyometric training and control group, weight training and control group since the p lt; 0.05. On the basis of findings of the study it may be considered that Plyometric training could be very much useful method of training for sportsman to improve vertical jumping ability and to retain the same for a longer duration.